Family's experiences of their children's nutritional health and wellbeing among food-insecure households in Europe: a qualitative systematic review and meta-ethnography. (November 2022) - Bell, Zoë; Scott, Steph; Visram, Shelina; Rankin, Judith; Bambra, Clare; Heslehurst, Nicola
Abstract: Background: There has been a rise in food insecurity in Europe since the 2008 global financial crisis and households with children are particularly vulnerable. We aimed to explore families' experiences of food insecurity and how these experiences affect children's nutritional health and wellbeing. Methods: In this systematic review and meta-ethnography, we searched Medline, Scopus, Web of Science, EMBASE, CINAHL, and ASSIA from Jan 1, 2008, to July 10, 2021, supplemented by grey literature, reference lists, and citation searches. Screening was done in duplicate to ensure consistent application of inclusion criteria and minimise random errors. Following title and abstract screening, full texts were screened against the inclusion criteria (qualitative research focussing on children's nutritional health and wellbeing, with data from 2008 onwards, from high-income European countries). Data extracted included study design, country of origin, caregiver type, gender, age, ethnic group, migration status, accommodation type, measure of food insecurity and other socioeconomic factors. Data were synthesised according to Noblit & Hare's seven phases of meta-ethnography. Our protocol was registered with PROSPERO (CRD42020214159). Findings: We identified 11 589 unique records; 19 were included, involving 813 participants. We identified four key themes: food and eating practices, awareness, fragility, and networks of care. Within the key themes, we identified five subthemes: diet, compromised infant feeding practices, psychological fragility, social fragility, and physical fragility. We found that children with food insecurity were aware of their family's scarce resources, with most active in trying to help their family while also forming their own networks of care. We found that food insecurity adversely affects children's physical, psychological, and social experiences setting them on a trajectory towards sub-optimal health. Interpretation: Children's nutritional health and wellbeing is adversely affected by food insecurity. This meta-ethnography highlights gaps in our knowledge about children's nutritional health relating to a range of sociodemographic factors. There is a need to actively involve children in more research and policy. A strength and limitation of this review is the diverse range of included studies from different European contexts, in which contextual factors could have affected our findings. Funding: The Economic and Social Research Council.